2017
DOI: 10.1021/acsami.7b09648
|View full text |Cite
|
Sign up to set email alerts
|

Superior Selective CO2 Adsorption of C3N Pores: GCMC and DFT Simulations

Abstract: Development of high-performance sorbents is extremely significant for CO capture due to its increasing atmospheric concentration and impact on environmental degradation. In this work, we develop a new model of CN pores based on GCMC calculations to describe its CO adsorption capacity and selectivity. Remarkably, it exhibits an outstanding CO adsorption capacity and selectivity. For example, at 0.15 bar it shows exceptionally high CO uptakes of 3.99 and 2.07 mmol/g with good CO/CO, CO/H, and CO/CH selectivity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(25 citation statements)
references
References 47 publications
1
23
1
Order By: Relevance
“…Similarly for NO 2 and NH 3 , E a is significantly lower than that of graphene. Among all the molecules considered in the present investigation, the adsorption strength for CO 2 is very high suggesting that C 3 N can be a good candidate for detecting CO 2 which also agrees with the high CO 2 uptake capacity reported through Grand Canonical Monte Carlo Calculations 8 . The adsorption strength for NO and SO 2 are also large, suggesting the usefulness of C 3 N for sensing these molecules.…”
Section: Electrostaticssupporting
confidence: 89%
See 1 more Smart Citation
“…Similarly for NO 2 and NH 3 , E a is significantly lower than that of graphene. Among all the molecules considered in the present investigation, the adsorption strength for CO 2 is very high suggesting that C 3 N can be a good candidate for detecting CO 2 which also agrees with the high CO 2 uptake capacity reported through Grand Canonical Monte Carlo Calculations 8 . The adsorption strength for NO and SO 2 are also large, suggesting the usefulness of C 3 N for sensing these molecules.…”
Section: Electrostaticssupporting
confidence: 89%
“…For this reason, Carbon(C)-Nitrogen(N) compounds with different N/C ratio is an area of huge interest due to their structural similarity to that of graphene. Out of the various combinations, monolayer polyaniline (C 3 N) was found to be a hole-free, 2D layered structure with fascinating electronic [2][3][4][5] , thermal 6,7 , mechanical 4 and chemical [8][9][10][11] properties, which was recently synthesised by direct pyrolysis 12 and polymerisation 13 process. In this structure, C 3 N forms a hexagonal honeycomb lattice similar to that of Graphene with an indirect band structure, unlike Dirac Fermions 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies reported that the presence of water molecules (humidity) and other gas molecules does not show a great influence on the gas sensing properties of 2D materials. [ 70,71 ] Based on these assumptions, we believe that the adsorption of COCl 2 on pristine and defective Ti 2 C(OH) 2 with the presence of other gas molecules may not alter their sensing features.…”
Section: Resultsmentioning
confidence: 99%
“…For example, amorphous carbon sheets are often used to find the best adsorption site and calculate the adsorption energy. Graphitic slit pore model consists of two layers of amorphous carbon sheets, which are widely used to study the effects of functional group doping and pore size on the adsorption [18][19][20]. Chen et al deeply studied the synergistic effects of functional groups and pore size on CO 2 adsorption by using it [21].…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%